Red Monday: The Silencing of Claudia Jones in 20th Century Feminist Revolutionary Thought. (1st July 2019) - Lindsey, Lydia
Abstract : The Cold War muzzled Claudia Jones' voice, one of the most significant women of the twentieth century, but the rediscovery of her writings and activism offers us new challenges to understanding her epistemology in the 21st century, especially in regard to 'super-exploitation' and tripartite sense of oppression, both of which are at the root of intersectionality. The concept of tripartite oppression is intergenerational. In recent years, Jones has been credited with popularizing the idea of the triple oppression of Black women based on their race, class, and gender, but Louise Thompson Patterson used the term in an essay, in the same year that Jones joined the Communist Party. Patterson appears to use the term triply-oppressed in reference to reforming, the conditions of domestic workers. Whereas Jones' writings and activism connected tripartite ideology to the peace movement. Jones linked the questions of race, class, and gender, to anti-colonialism, anti-imperialism, and anti-fascism into a singular struggle to attain peace that would create an egalitarian society which makes her the mother of global revolutionary thought. The concept of triply-oppressed is not static. It embodies a degree of dynamism as it situates in the context of time and space; so that in the twenty-first century lexicon the concept is expressed in terms of intersectionality.